Gambaran Pengetahuan Ibu Tentang Manajemen Laktasi di Rumah Sakit Santa Elisabeth Medan - Nadeak, Lilia Twin; Br. Barus, Mardiati; Br. Ginting, Friska (JURNAL KEPERAWATAN MERSI, 2023)
Background: Lactation management is an effort made to help mothers achieve success in breastfeeding so that babies can be breastfed properly and correctly, especially exclusive breastfeeding. Lactation management begins during pregnancy (antenatal), after delivery (perinatal) and during breastfeeding until the child is two years old. Implementation of breastfeeding can be done properly and correctly if there is complete information about the benefits of breastfeeding and lactation management. Exclusive breastfeeding is inhibited by several things such as breastfeeding behavior that is less supportive about lactation management, awareness of the importance of breastfeeding. If lactation management is not carried out, it will have an impact on reducing breastfeeding so that it will have an impact on increasing rates of malnutrition and undernutrition which are at risk of increasing infant morbidity and mortality. Objective: This research aims to determine the factors that influence exclusive breastfeeding. Methods: This research design is descriptive analytic, which aims to describe (describe) important events that occur in the present. Event descriptions are carried out systematically and emphasize factual data rather than conclusions (Nursalam, 2014). Results: Based on the results of research conducted on "Description of Mother's Knowledge About Lactation Management at Santa Elisabeth Hospital Medan" it was concluded that the level of knowledge of the respondents was sufficient, namely as many as 17 respondents (56.6%). This is influenced by the age, education, occupation of the respondent and the lack of information about the mother regarding lactation management. For this reason, it is hoped that pregnant women and breastfeeding mothers can increase their knowledge about pregnancy and successful breastfeeding both from health books and from health workers. Conclusion: The results of this research concluded that 9 people (30%) had good knowledge, 17 people (57%) had sufficient knowledge, while 4 people had insufficient knowledge (13%).